The motives of the implementation of Tarekat Tijaniyah in Islamic boarding school from Alfred Schutz's perspective - Kuswandi, Iwan; Tobroni,; In’am, Akhsanul; Khozin,; Asmoni,; Fauzi, Moh; Jamilah,; Puspitorinij, Agusriyanti (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper identifies the thoughts of Kiai Djauhari, Kiai Tidjani and Kiai Ahmad Fauzi in interpreting their experiences and obsessions as practitioners of Tarekat Tijaniyah (ideology in the world of Sufism or Islamic Sufism) based on their family historical background, lifetime, domicile, affiliation, intellectual background and their future aspirations. This study uses a phenomenological study at al-Amien Prenduan Islamic Boarding School. The data were collected through observation, interviews and documentation, then the research findings were analyzed using Alfred Schutz's Phenomenological theory. The conclusion of this study is that the family backgrounds of Kiai Djauhari, Kiai Tidjani and Kiai Ahmad Fauzi are families who practice tarekat. Kiai Djauhari's educational background was in traditional Islamic boarding school (Annuqayah Guluk-guluk, Tebuireng Jombang and Sidogiri Pasuruan), while Kiai Tidjani and Kiai Ahmad Fauzi graduated from modern Islamic boarding school (Pondok Gontor Ponorogo). All three have also studied in Saudi Arabia although with different majors and levels. Kiai Djauhari used to be active in practical politics through Masyumi Party on the other hand, both Kiai Tidjani and Kiai Ahmad Fauzi have neutral stance in politics. Kiai Djauhari's aspiration was to build a modern Islamic boarding school like Gontor, while Kiai Tidjani and Kiai Ahmad Fauzi's obsession is maintaining traditional values in the modern system.